STRATEGI ORANG TUA DALAM MENANAMKAN NILAI-NILAI AKHLAK TERHADAP ANAK DI ERA ALFA ( Studi Kasus Di Kampung Gemilang RT 02) - Titi Nur Afifah (KOLONI, 2023)
Parents are the main educators for their children, so it is from parents that children receive the most influential lessons (guidance) for their future. Parents, or mothers and fathers, play the most important role and are very influential in instilling morals. The purpose of this research was to analyze the strategies used by parents in instilling moral values in children, analyze obstacles, and solve solutions to the obstacles faced. The method used in this research uses a case study-descriptive approach. The data sources in this research were informants from parents who had problems related to the cultivation of morals in Kampung Gemilang Rt 02. The data collection techniques used were interviews and documentation. Data analysis used data reduction, selecting, focusing, abstracting, and simplifying. The results of the research show that the strategy used by parents in Kampung Gemilang to instill moral values in children is by providing exemplary learning methods for children, providing the best education through madrasah, and having light discussions with children. The obstacles or constraints faced by parents are the attitude of children who tend to disobey parents and the influence of gadgets. The solutions include parents being role models in life, having light discussions, increasing patience in teaching children morals, and providing good education through madrasa education.